Complex moral dilemmas of large scale development projects: the case of Macdom-ARDA Chisumbanje ethanol project in Chipinge, Southeastern Zimbabwe - Konyana, Elias G.; Sipeyiye, Macloud (Inderscience, 2018)
Elitist socio-economic policies are largely responsible for community displacements in Africa. Historically, colonial governments’ land-intensive projects were major disruptive phenomena for the affected communities. Practically, however, displacement unsettles communities, upsets cultural or traditional practices, justice systems and communal livelihoods. Quite often, communal displacement represents low regard for human rights by state and non-state actors. Ironically, planners of displacements often adopt and deploy the rhetoric of sustainable development and modernism. In Zimbabwe, the persistent conclusion in displacement narratives is that land dispossessions pushed Africans into supporting the nationalist movements of the 1960s and he liberation struggle that followed. However, post-independence joint projects have continued to haunt communities. This paper presents moral issues associated with development-induced displacements and resettlement It provides communal narratives emanating from the Public-Private Partnership Macdom-ARDA Chisumbanje ethanol project, arguing that the project is morally objectionable insofar as it is responsible for the displacement of thousands of local people.